Heracles perplexed or perennial adolescence. (Journal of Parents and Teachers, 2013)
This article talks about one of the formative “bads” of our time: inattention of the constitution of the “moral character” of young people. This is linked to the abandonment of the teleological thought in return of instruments that has had place in our societies lately. This has as consecuence a consecuent disrespect of the purpose of the own life which is the only thing that a person can achieve to fulfil oneself fully as a human being. This article also brings up the need of a reformulation on a positive and valorative background of the grecolatine concept of “virtue”. This means that there is a need of training of the moral character, and in this order, the importance of the effective route of being exemplary is emphasize. To explain this, the author uses a mithical story called “Choice of Hercules” that was written by the greek sofist Pródico de Queos and that it is reproduce in the Memorabilia by Xenophon.
Keywords: Ethics; Moral development; Conscience; Freedom; Identity.